Development of Lecture Attendance System Using QR Code in Information and Computer Engineering Education Study Program of Universitas Negeri Makassar - Tenri Nadya Wenny; Suhartono Suhartono; Jumadi Mabe Parenreng (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
This research is a software development research that aims to develop a lecture attendance system because from the past until now the computer engineering and informatics education study program did not have an attendance database, therefore the attendance data collection itself was done manually which could trigger human error and attendance fraud which is often done by students. Therefore it is necessary to develop a student attendance information system using a QR Code. The application quality based on ISO 9126 quality standards. In this study, system data analysis and collection, prototyping, prototyping, system coding, system testing, system evaluation, and system use. Data was collected using interviews, observation, and survey techniques. The system was validated by two system experts and evaluated by 40 students from the In-formation Technology and Computer Engineering study program at UNM. Data analysis used descriptive statistical analysis techniques. Based on these findings, we created an application that can manage wedding guest data. Based on the test results, you will get the following results: (a) Very good functionality in this category; (b) The maintainability aspect has met the maintainability standard; (c) The portability aspect is rated 1 or very good category; (d) Aspect of reliability with a percentage value of 99.9 so that it meets the reliability standards set in the Telcordia standard; (e) The efficiency aspect of this application is Grade B with a performance percentage of 83; and (f) The system user rating (usability aspect) has a score of 88.05 or very good in the category.